The Impact of Fuel Increase and Currency Exchange Depreciation on Indonesia Aviation Industry Sustainability - Simarmata, Juliater; A.N, Charles; Rizaldy, Wynd (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2014)
Population growth after the crisis of 1998, was accompanied by a very encouraging economic growthreaching 6.3% during 2012. Accordingly, the development of the aviation industry continues to increase rapidly, this is evidenced by the emerging new airlines such as AW Air, Jatayu Air, Lion Air, Star Air which was followed by Batavia Air, Sriwijaya Air, Adam Air, Water Aerfata Papua, which makes the competition between one another takes place very tighty. Through the methods of qualitative and quantitative research design and analysis of rate of expansion which is explorative description, then it is clearly visible that only airlines with appropriate strategies that can survive in the midst of the world economic shocks, especially aviation fuel price increases that occurred every two weeks and the weakening of the rupiah against the dollar . The strategy implemented is related with fuel conservation policy; such as applying Cost Index, Tankering Fuel, Optimum Level Flight elections, focusing on flight technic and maintenance in order to improve efficiency in the use of fuel or aviation fuel, or even change the type of aircrafts.